Effect of migration of layered nanoparticles during melt blending on the phase morphology of poly (ethylene terephthalate)/polyamide 6/montmorillonite ternary nanocomposites. Issue 38 (30th March 2015) - Xu, Guomin; Qin, Shuhao; Yu, Jie; Huang, Yifu; Zhang, Mingqiu; Ruan, Wenhong
Abstract : Migration and selective localization of layered nanoparticles during melt compounding have great influence on phase morphology of polymer blends. Abstract : To study the effect of migration and selective localization of layered nanoparticles during melt compounding on the phase morphology of polymer blends, poly (ethylene terephthalate) (PET)/polyamide 6 (PA6)/organic montmorillonite (OMMT) ternary nanocomposites were prepared. Three different blending sequences were adopted either by pre-compounding OMMT into PET or into PA6 or by mixing all three components together. The morphology and tensile properties of PET/PA6/OMMT nanocomposites were investigated. TEM observation showed that OMMT platelets exclusively localized within the PA6 phase independent of the blending sequences, suggesting OMMT platelets migrated from PET into the PA6 phase during both the one-step and two-step compounding processes with pre-mixed PET/OMMT, and this migration was attributed to interfacial effects. SEM results revealed that the migration and selective localization of OMMT platelets had great influence on the size of the dispersed phase due to the conjunct action of the migration cutting effect and viscosity effect. The morphology determines the final properties of the nanocomposites as indicated by tensile test. It is believed that this work provides a way to tune the morphology and performance of immiscible blends.